The Road to Bloody Sunday : The Role of Father Gapon and the Petersburg Massacre of 1905 - Sablinsky, Walter, 1929- (Book collections on Project MUSE., 1976)
Drawing on all available documents, Walter Sablinsky reappraises the events, especially the role of the volatile and often unpredictable Father Gcorgii Gapon. the young Orthodox priest who inspired and led the workers' organization. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editi.